The Effect of Different Types of Plant Media Composition on Growth And Physiology of Tomato - Slamet Rohadi Suparto; Rama Adi Pratama; Yesira Setyo Palupi; Etik Wukir Tini (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
The study aims to determine the effect of several planting media on the growth and physiology of tomato plant seedlings except for soil. This research was conducted from March to May 2021 at the Greenhouse and Laboratory of Agronomy and Horticulture, Faculty of Agriculture, Jenderal Sudirman University, Purwokerto. The research method was the Completely Randomized Block Design (CRBD) with one factor and three replicated designs. The data obtained were analyzed using the F test with a 5% level, followed by Duncan's Multiple Range Test (DMRT) with a 5% level. The result shows that the planting medium of husk ash and compost (1:1) gave the best effect on average several observation parameters on plant height 25.17 cm, number of leaves 25 strands, leaf area 12.75 cm2, fresh crown weight 6.55 g, dry crown weight 1.32 g, root length 17.92 cm, fresh root weight 0.86 g, dry root weight 0.286 cm. While, the average relative growth rate of 0.341 g/day, and the net assimilation rate was 0.036 g/cm2/day. Other results showed that the composition of the planting media which includes a combination of sand, cocopeat, burnt husks, husk ash, and compost has an influence on the growth and physiology of seedlings but does not increase the chlorophyll content and greenness of the leaves of tomato plant seeds.